The Legality of Border Shifts Due to Coastal Reclamation - Dita Birahayu (Hang Tuah Law Journal, 2018)
Based on Declaration of Djuanda, it declared that Indonesia maritime was defined as the entity of the Republic of Indonesia (NKRI), and thus, Indonesia is known as an archipelagic country with a very broad maritime territory directly adjacent to 10 neighboring countries. However, it poses a lot of potential maritime boundary conflict. Supported by this current advanced science, both artificial islands and coastal reclamation were being carried out. Singapore is one having a reclamation named Jurong Island, and it is very close to the territory of NKRI. As an independent country, Indonesia is attempting to protect its territory by having a diplomatic negotiation with Singapore in order to decide the legal certainty over their maritime borders, especially in east area. In addition, they need to define the legal status of that reclaimed island. Based on UNCLOS 1982 article 11 and 80, the legal status of the reclaimed island may not threaten the sovereignty of NKRI as its presence does not change the maritime territory of a country, and it has been agreed in the previous agreement.